Evidence for different ABC-transporters in caco-2 cells modulating drug uptake - Gutmann, Heike; Fricker, Gert; Török, Michael; Michael, Susanne; Beglinger, Christoph; Drewe, Jürgen (Pharmaceutical research, 1999)
Purpose. Secretory systems contribute to drug absorption in the gastrointestinal tract. The purpose of this study was the identification of members of the ATP binding cassette superfamily of secretory transport proteins that may potentially modulate drug absorption in Caco-2 cells, which are an important cellular model predicting enteral absorption of drugs.Methods. Kinetic studies as well as PCR- and Western blot studies with confluent epithelial layers of human Caco-2 cells.Results. The study demonstrates functional expression of multidrug resistance related protein (MRP) and P-glycoprotein (P-gp) in Caco-2 cells: 1) Efflux studies with the MRP specific substrate glutathion-methylfluorescein (GS-MF) showed functional activity of MRP in Caco-2 cells preloaded with the metabolic precursor of GS-MF, chloro-methylfluoresceine-diacetate, CMFDA. Excretion of GS-MF was decreased in presence of the MRP-blocker MK-571.2) Transport experiments with cyclosporin A demonstrated the functional activity of P-gp. Cellular accumulation was increased in presence of the P-gp blocking agent SDZ-PSC 833.3) The expression of the 190 kDa protein MRP and the 170 kDa protein P-gp in Caco-2 cells was shown by Western blot analysis with specific monoclonal antibodies. 4) The expression of MRP-mRNA in Caco-2 cells was detected by RT-PCR and compared with the MRP over-expressing cell line H69AR. MRP primers recognize specifically human MRP1 (GenBank accession number L05628), but not all other published sequences of MRP (MRP2-MRP6). P-gp expression on mRNA-level was also confirmed by RT-PCR.Conclusions. The data demonstrate that besides P-gp, multidrug resistance related protein (MRP) is functionally expressed in Caco-2 cells and contributes to the active excretion of substrates in this cell line.
Gesehen am 26.04.2017